2020
DOI: 10.1097/ncc.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Factors Associated With Reproductive Concerns in Younger Female Cancer Patients

Abstract: Background Cancer treatments may compromise fertility and family building in reproductive-age women. Previous research has shown that younger women with cancer experienced several reproductive health concerns. Objective The aim of this study was to conduct a focused review of existing research about the subjective perceptions of reproductive concerns among young women with cancer (aged 15-49 years) and identify their potential predictors and outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(189 reference statements)
0
5
0
Order By: Relevance
“… 22 , 24 The genetic risk factor of cancer was also a concern among patients with breast cancer as the disease and treatment would not only affect their health but also the health of their children. 43 , 44 Therefore, patients with reproductive concerns had a weaker fertility intention. Overall, the convergent validity of the FIS is not satisfactory and further revision and validation are required in the future.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 24 The genetic risk factor of cancer was also a concern among patients with breast cancer as the disease and treatment would not only affect their health but also the health of their children. 43 , 44 Therefore, patients with reproductive concerns had a weaker fertility intention. Overall, the convergent validity of the FIS is not satisfactory and further revision and validation are required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A study of female patients aged 15-49 years with breast cancer links reported RHC to symptoms of depression and quality of life. 24 In this study, we examine RHC of AYA living with a variety of chronic conditions at earlier stages of their reproductive lives and find associations between RHC and health-related stress and anxiety. What we cannot determine is how elevated RHC and associated health-related stress and anxiety might also be related to risk-taking and decision-making that might impair healthy sexual functioning and reproductive health planning.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean age of the sample was 36 years, limiting our understanding of the relationship of RHC and mental health and HRQoL among AYA who are in the formative stages of contemplating their reproductive futures. 24 The authors' systematic review of RHC studies among women aged 16 to 49 years who have survived breast cancer suggests that RHC in the early stages of survivors' reproductive lives differ from older women. As we are now seeing that AYA with chronic health conditions are as sexually active and as interested as their healthy peers in starting a family, it is important to explore their concerns and stressors as they begin considering having and raising children and understand how these concerns may be associated with HRQoL and stress.…”
mentioning
confidence: 99%
“…Reproductive concerns among cancer patients are influenced by many factors including personal circumstances and previous treatments (Bártolo et al, 2021). Patients' satisfaction with the extent to which their need for fertility‐related information is met is also thought to be closely related to their degree of reproductive concern.…”
Section: Background and Aimmentioning
confidence: 99%